The impact of statins on health services utilization and mortality in older adults discharged from hospital with ischemic heart disease: a cohort study - Sketris Ingrid S; Kirkland Susan A; Cooke Charmaine A; Cox Jafna (BMC, 2009)
Abstract Background Cardiovascular disease (CVD) carries a high burden of morbidity and mortality and is associated with significant utilization of health care resources, especially in the elderly. Numerous randomized trials have established the efficacy of cholesterol reduction with statin medications in decreasing mortality in high-risk populations. However, it is not known what the effect of the utilization of these medications in complex older adults has had on mortality and on the utilization of health services, such as physician visits, hospitalizations or cardiovascular procedures. Methods This project linked clinical and hospital data from the Improving Cardiovascular Outcomes in Nova Scotia (ICONS) database with administrative data from the Population Health Research Unit to identify all older adults hospitalized with ischemic heart disease between October 15, 1997 and March 31, 2001. All patients were followed for at least one year or until death. Multiple regression techniques, including Cox proportional hazards models and generalized linear models were employed to compare health services utilization and mortality for statin users and non-statin users. Results Of 4232 older adults discharged alive from the hospital, 1629 (38%) received a statin after discharge. In multivariate models after adjustment for demographic and clinical characteristics, and propensity score, statins were associated with a 26% reduction in all- cause mortality (hazard ratio (HR) 0.74, 95% confidence interval (CI) 0.63-0.88). However, statin use was not associated with subsequent reductions in health service utilization, including re-hospitalizations (HR, 0.98, 95% CI 0.91-1.06), physician visits (relative risk (RR) 0.97, 95% CI 0.92-1.02) or coronary revascularization procedures (HR 1.15, 95% CI 0.97-1.36). Conclusion As the utilization of statins continues to grow, their impact on the health care system will continue to be important. Future studies are needed to continue to ensure that those who would realize significant benefit from the medication receive it.